Prevalence of solid tumors and lymphoma in the Brazilian Sjögren’s Disease Registry (BRAS): an important concern for clinical practice - Virginia Fernandes Moça Trevisani; Fabiola Reis de Oliveira; Sandra Gofinet Pasoto; Laura Caldas; Roberta de Almeida Pernambuco; Alisson Pugliesi; Leandro Augusto Tanure; Juliana Markus; Maria Lúcia Lemos Lopes; Aysa César Pinheiro; Vanessa Hax; Aiessa Zanchett Fedrigo; et al. (Advances in Rheumatology)
Abstract Background About 5–10% of patients with Sjögren’s Disease (SjD) will develop non-Hodgkin’s lymphoma, with a 16 to 44 increased risk compared to the general population. The relationship between SjD and other types of cancer is poorly described in the literature. Aim To characterize patients with SjD from the Brazilian Sjögren’s Disease Registry (BRAS) who developed hematological and solid neoplasms, analyzing the organ primarily involved, subtypes, occurrence of metastatic disease, timing of diagnosis and correlation with demographic, serologic aspects, and labial salivary gland inflammation. Methods Among consecutive patients included in the Brazilian Sjögren’s Disease Registry (BRAS) and fulfilling the 2002 or 2016 classification criteria for SjD, those who developed neoplasia were retrospectively identified and categorized according to the National Cancer Institute (Ministry of Health, Brazil). RESULTS: 1,010 patients were included; of them, 975 were women (96.5%), with an average age of 55.6 ± 13.6 years. Disease duration was 11.9 ± 7.9 years. We found that 114 out of 1,010 patients (11.3%) had cancer, with a higher prevalence in those over 55 years old (p < 0.001). The most prevalent malignancies were skin cancer [24/858 (2.7%)], breast cancer [27/1010 (2.6%)], lymphoma [15/1010 (1.5%)], and thyroid cancer [8/1010 (0.8%)]. Further, 0.9% of patients had more than one type of cancer. Cancer diagnosis followed SjD diagnosis in 66.7% of lymphoma cases, 53.6% of other malignancies, and 75.0% of skin cancer. The presence of cancer was associated with age (OR 1.04). In the case of skin cancer, the duration of SjD was an additional risk factor (OR 1.08). For thyroid cancer, inflammation of the labial minor salivary glands was identified as an associated risk factor (OR 10.1). Conclusions Other types of cancer were more prevalent than lymphoma in our population of SjD patients. Breast neoplasia emerged as the most prevalent after skin cancer, and thyroid cancer was the second most prevalent solid neoplasia. Aging, disease duration and labial salivary gland inflammation were associated risk factors. Prospective cohort studies are essential for assessing other risk factors for cancer development in SjD patients.